Post-harvest losses and welfare of tomato farmers in Ogbomosho, Osun state, Nigeria (2014)
Crop losses, especially along the post-harvest food supply chain, have been identified as one of the major causes of food shortage problems in most developing countries and in Nigeria in particular. Vegetable farmers such as those that grow tomatoes often record great amount of produce loss which translates to a waste of resources, a reduction in their income and ultimately their welfare. This study examined the effects of post-harvest losses on the welfare of 107 tomato farmers in Ogbomosho selected through a multi-stage sampling procedure. The analytical tools used in the study include descriptive statistics, gross margin analysis, Ordinary Least Square (OLS) and regression model. Results revealed that majority of the tomato farmers were male, married and had no formal education. The average gross margin values of N3, 229.45 and N72, 905.80 were obtained with and without postharvest losses for the tomato farmers respectively. This implied a 95.5% post-harvest loss incurred by the farmers. Household size and the total value of post-harvest losses were found to significantly affect the per-capita income and hence welfare of the tomato farmers negatively. The study recommends that farmers engaged in tomato production be adequately trained on post-harvest crop handling techniques. In addition, priority should be given to investment in post-harvest processing technologies and establishment of processing industries especially in the production areas.